Skin surface infrared thermography in pressure ulcer outcome prognosis. (2nd December 2020) - Bilska, Anna; Stangret, Aleksandra; Pyzlak, Michal; Wojdasiewicz, Piotr; Szukiewicz, Dariusz
Abstract : Objective: To assess the usefulness of skin surface infrared thermography (SSIT) as a prognostic tool in the treatment of stages III and IV pressure ulcers (PU), with hydrocolloid/hydrogel dressings plus 20 exposures to low-level laser therapy (LLLT), compared with hydrocolloid dressings alone, in a group of long-term bedbound care patients. Method: In this comparative study, participants were randomly assigned to group I: PUs treated with specialist wound dressings and laser therapy, or to group II: PUs treated with specialist wound dressings without laser therapy. Thermal imaging sessions were carried out at the beginning of the study, and after two and four weeks of treatment. Thermal imaging processing was applied to compare percentage differences in the temperature distribution between the groups within selected regions of interest (ROIs). The correlation between the temperature distribution and PU healing was evaluated. Results: A total of 43 patients took part. In the study, three variants of PU healing were observed: pure healing (H) with minimal granulation; healing with hypergranulation (H+G); and non-healing (NH). Analyses of SSIT-related thermographic patterns revealed their dependence on the course of healing. The percentage of successful PU healing reached 79.2% in group I compared with 73.7% in group II (p<0.05) The dominant variant of healing in Group I was H, while in group II the variants H and H+G were present with equal frequency. Conclusion: Thermal imaging processing allowed comparison of differences in the temperature distribution between the groups within ROIs. Application of LLLT significantly improved the healing process (p<0.05). The clinical significance of this finding should be confirmed with larger studies; however, SSIT may be useful as a prognostic tool during the treatment of PUs, with the ability to predict the course of healing initially, that is independent of LLLT treatment.